THE INFLUENCE OF INTRINSIC MOTIVATION AND EMPOWERMENT ON AFFECTIVE COMMITMENT AND ITS IMPLICATIONS FOR ORGANIZATIONAL CITIZENSHIP BEHAVIOR - E. Fitrah Nurkamilah; Kartawan, Yusuf Abdullah (Adisam Publisher, 2024)
This study aimed to identify the effect of intrinsic motivation and empowerment on affective commitment and its implication on organizational citizenship behavior. The research method used an explanatory with a quantitative approach and descriptive method to know category of these research construcs. The research sample amounted to 200 people of the employees of The Perumda in East Priangan. The sampling technique used a proportional random sampling technique. Data collection techniques used observation methods and questionnaire distribution. Research data in the form of primary and secondary data. Data analysis techniques used the Structural Equation Model (SEM) using the Smart Pls analysis tool. The results indicated that (1) intrinsic motivation and empowerment had effect on affective commitment; (2) intrinsic motivation and empowerment had effect on organizational citizenship behavior; (3) affective commitment had effect on organizational citizenship behavior; and (4). intrinsic motivation and empowerment had effect on organizational citizenship behavior that mediated by affective commitment of the employees of Perumda in East Priangan.